Association Between Single-Nucleotide Polymorphisms in Toll-like Receptor 3 (tlr3), tlr7, tlr8 and tirap Genes with Severe Symptoms in Children Presenting COVID-19 - Adriana Souza Andrade; Aline Almeida Bentes; Lilian Martins Diniz; Silvia Hees Carvalho; Erna Geessien Kroon; Marco Antonio Campos (Viruses)
The global number of COVID-19 deaths has reached 7 million, with 4% of these deaths occurring in children and adolescents. In Brazil, around 1500 children up to 11 years old died from the disease. The most common symptoms in children are respiratory, potentially progressing to severe illnesses, such as severe acute respiratory syndrome (SARS) and MIS-C. Studies indicate that comorbidities and genetic factors, such as polymorphisms in immune response genes, can influence the severity of COVID-19. This study investigates the occurrence of single-nucleotide polymorphisms (SNPs) in innate immune response genes in children with COVID-19. Seventy-three samples were analyzed from children under 13 years old hospitalized at João Paulo II Children’s Hospital due to COVID-19. The evaluated SNPs were tlr8 (1) (rs3764879), tlr8 (2) (rs2407992), tlr7 (rs179008), tlr3 (rs3775291), tirap (rs8177374), and mcp-1 (rs1024611), considering four categories of severity: mild, moderate, severe, and critical COVID-19. To identify the SNPs, PCR and sequencing were performed. The frequencies of the SNPs obtained were not discrepant when compared to the frequencies described in the Global ALFA, Global 1000 Genomes, Global gnomAD, American 1000 Genomes, and American gnomAD databases, except for the SNP in TLR7. Comparing severe and critical cases to mild and moderate cases, we found a higher relative risk associated with mutations in tlr8 (1), tlr7, tlr3, and tirap (p < 0.05). No association was found for SNPs in tlr8 (2) and mcp-1. Our analyses suggest an association between SNPs in innate immune response genes and severity of symptoms in children with COVID-19 (or SARS-CoV-2 infected children).